Pi Museum: an Educational Escape Room for Learning Mathematics - Irene Araújo; Sónia Pais; Andreia Hall (Indagatio Didactica)
This paper presents the implementation of a virtual educational escape room (EER) titled “Pi Museum”, designed to promote interactive mathematics learning within the context of the International Day of Mathematics, celebrated on March 14th, also known as Pi Day. The EER was developed on the Genially platform and applied to 6th-grade classes in a Portuguese school as a formative assessment tool. The escape room’s theme was structured to reinforce students’ knowledge of the number Pi, its history, and applications, as well as to consolidate concepts of perimeter, area, and volume, always involving the number Pi whenever possible. The experience showed that gamification facilitates knowledge acquisition, improves student motivation, and fosters teamwork. The results indicate that students felt engaged and motivated, rating the experience as enriching and fun. The methodology used was based on solving interactive mathematical challenges, promoting an innovative approach to teaching. The EER also offered the possibility of developing transversal skills, which are fundamental for students’ overall development.